Financial Distress Prediction in Infrastructure, Utilities, and Transportation Sector Companies 2015-2020 - Mashudi, Mashudi; Himmati, Risdiana; Ardillah, Id Fitria Rahayu; Sarasmitha, Citra (University of Merdeka Malang, 2021)
This research is based on financial distress or financial distress, which negatively impacts the company, marked by its inability to fulfill its obligations at maturity. This phenomenon can be an early warning related to further problems, and financial distress can be overcome by predicting as early as possible. This prediction is essential for management and company owners to anticipate potential bankruptcy. The formulations in this study include whether inflation affects predicting financial distress in companies in the Infrastructure, Utilities, and Transportation sectors listed on the IDX for the 2015-2020 period. And Whether the financial ratios (Current Ratio, Debt To Equity Ratio, Total Asset Turn Over, Return on Equity, Price Book Value) affects predicting financial distress in Infrastructure, Utilities, and Transportation sector companies listed on the IDX the 2015-2020 period. This study uses a quantitative approach and the type of associative research, and the source data is secondary data with a sample of 10 companies. The sampling technique used purposive sampling. Data processing in this study uses E-Views 9 with Panel Data Regression analysis techniques. This study can conclude that the variables of inflation, current ratio, price-book value, and total turnover significantly affect financial distress in the Infrastructure sector companies: utilities and Transportation. Meanwhile, the debt to equity ratio and return on equity variables did not substantially affect financial distress in the Infrastructure, Utilities, and Transportation sector companies in 2015-2020.DOI: 10.26905/jkdp.v25i3.5858